Comparing Outcomes of Systemic Anticoagulant Therapy and Vascular Interventional Therapy in Cerebral Venous Sinus Thrombosis with Concurrent Brain Parenchymal Injury: Biomarker Analysis: Prognostic value of serum caspase-cleaved cytokeratin-18 (CCCK-18), neuron-specific enolase (NSE), S-100β, nerve growth factor (NGF) and CRP, D-Dimer, EPO - Cheng, Xiangjie (Journal of Medical Biochemistry, 2025)
Introduction: it was to investigate the clinical effectiveness of neurovascular interventional thrombectomy for treating cerebral venous sinus thrombosis (CVST) with concurrent brain parenchymal injury and evaluate Prognostic value of serum caspase-cleaved cytokeratin-18 (CCCK-18), neuron-specific enolase (NSE), S-100β, nerve growth factor (NGF) and CRP, D-Dimer, EPO. Materials and Methods:Ninety patients with CVST combined with parenchymal brain damage were randomly divided into the systemic anticoagulant therapy group (SAT group) and the vascular interventional therapy group (VIT group), with 45 patients in each group. The SAT group received only systemic anticoagulant therapy, while the VIT group received systemic anticoagulant therapy combined with neuroendovascular thrombectomy. Three months after discharge, mRS, NIHSS, GCS, and patients’ quality of life were assessed. Peripheral blood samples were collected to measure changes in CRP, D-Dimer, EPO, and caspase-cleaved cytokeratin-18 (CCCK-18) levels. The levels of serum neuron-specific enolase (NSE), S-100β, and nerve growth factor (NGF) before treatment and at 3 days and 7 days post-treatment were compared.Follow-up at six months post-discharge included calculations of mortality and recanalization rates, as well as evaluations of short-term prognosis. Results:In the VIT group, the proportion of patients with an mRS ≥ 2 at 3 months post-discharge was 11.1%, compared to 35.6% in the SAT group, indicating a significantly lower proportion in the VIT group (P < 0.05). Additionally, compared to the SAT group, the VIT group had lower NIHSS scores, higher GCS and SF-36 scores, and lower levels of serum CRP, EPO, and CCCK-8 (P < 0.05). The levels of NSE and S-100β in the VIT group at 7 days post-treatment were significantly lower than those in the SAT group (P< 0.05), whereas the NGF levels at 3 days post-treatment were higher in the VIT group compared to the SAT group (P< 0.05).Follow-up revealed that the survival rates in the SAT and VIT groups were 88.9% and 95.6%, respectively (no significant difference). However, the proportion of patients with an mRS ≥ 2 was lower in the VIT group compared to the SAT group (20.0% vs. 42.2%), and the complete recanalization rate was higher in the VIT group (73.3% vs. 53.3%) (both P < 0.05). Conclusion: combined SAT with neurovascular interventional thrombectomy benefits patients with CVST and concurrent brain parenchymal injury by promoting recovery of neurological deficits and consciousness, achieving vascular recanalization.